Penelitian Kerugian Energi Pada Sistem Exhaust Manifolds Instalasi Pipa Air Bersih - Djalil, Muh. Afdal; Salimin, Salimin; Sudia, Budiman (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2019)
The purpose of this study is to determine the energy losses in the piping installation with the exhaust manifolds installation model in the clean water system. There is a research objective of this piping system to determine the effect of water discharge (Q) on head losses (Re) and the Reynolds number (Re) variation on loss coefficient (K), and know how much the value of water discharge (Q), head losses (h) and coefficient of loss (K), and the flow characteristics of the exhaust manifold system. In this study, the test material used is PVC pipe size 0.0127 m .and variations of testing of exhaust manifolds installation 35 cm-55 cm, each branch to determine the pressure on the measuring instrument manometer.Keywords: Energy, losses, pipe, water